Melatonin Mediates Protective Effects against Kainic Acid-Induced Neuronal Death through Safeguarding ER Stress and Mitochondrial Disturbance - Xue, Feixiao; Shi, Cai; Chen, Qingjie; Hang, Weijian; Xia, Liangtao; Wu, Yue; Tao, Sophia Z.; Zhou, Jie; Shi, Anbing; Chen, Juan (Frontiers in Molecular Neuroscience, 2017)
Kainic acid (KA)-induced neuronal death is linked to mitochondrial dysfunction and ER stress. Melatonin is known to protect hippocampal neurons from KA-induced apoptosis, but the exact mechanisms underlying melatonin protective effects against neuronal mitochondria disorder and ER stress remain uncertain. In this study, we investigated the sheltering roles of melatonin during KA-induced apoptosis by focusing on mitochondrial dysfunction and ER stress mediated signal pathways. KA causes mitochondrial dynamic disorder and dysfunction through calpain activation, leading to neuronal apoptosis. Ca2+ chelator BAPTA-AM and calpain inhibitor calpeptin can significantly restore mitochondrial morphology and function. ER stress can also be induced by KA treatment. ER stress inhibitor 4-phenylbutyric acid (PBA) attenuates ER stress-mediated apoptosis and mitochondrial disorder. It is worth noting that calpain activation was also inhibited under PBA administration. Thus, we concluded that melatonin effectively inhibits KA-induced calpain upregulation/activation and mitochondrial deterioration by alleviating Ca2+ overload and ER stress.